Effect of Centrifugation on Water Recycling and Algal Growth to Enable Algae Biodiesel Production. (1st December 2014) - Igou, Thomas; Van Ginkel, Steven W.; Penalver‐Argueso, Patricia; Fu, Hao; Doi, Shusuke; Narode, Asmita; Cheruvu, Sarasija; Zhang, Qian; Hassan, Fariha; Woodruff, Frazier; Chen, Yongsheng
ABSTRACT: : The latest research shows that algal biofuels, at the production levels mandated in theEnergy Independence and Security Act of 2007, will place significant demands on water and compete with agriculture meant for food production. Thus, there is a great need to recycle water while producing algal biofuels. This study shows that when using a synthetic medium, soluble algal products, bacteria, and other inhibitors can be removed by centrifugation and enable water recycling. Average water recovery reached 84% and water could be recycled at least 10 times without reducing algal growth.